2002
DOI: 10.1038/nature01063
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic defects in lymphocyte activation caused by caspase-8 mutations lead to human immunodeficiency

Abstract: Apoptosis is a form of programmed cell death that is controlled by aspartate-specific cysteine proteases called caspases. In the immune system, apoptosis counters the proliferation of lymphocytes to achieve a homeostatic balance, which allows potent responses to pathogens but avoids autoimmunity. The CD95 (Fas, Apo-1) receptor triggers lymphocyte apoptosis by recruiting Fas-associated death domain (FADD), caspase-8 and caspase-10 proteins into a death-inducing signalling complex. Heterozygous mutations in CD95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
526
1
13

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 645 publications
(562 citation statements)
references
References 28 publications
22
526
1
13
Order By: Relevance
“…4A). Several reports have suggested that caspases, in particular Caspase-8, not only play an essential role in apoptosis execution, but may also be important for T cell proliferation [25][26][27][28][29]. T cells lacking a functional FADD adaptor protein, either in FADD -/-knockout mice [12] or in transgenic animals overexpressing a dominantnegative FADD [16][17][18], exhibit a reduced proliferative capacity.…”
Section: Decreased Proliferative Capacity Of Lck Flip S -Transgenic Tmentioning
confidence: 99%
See 1 more Smart Citation
“…4A). Several reports have suggested that caspases, in particular Caspase-8, not only play an essential role in apoptosis execution, but may also be important for T cell proliferation [25][26][27][28][29]. T cells lacking a functional FADD adaptor protein, either in FADD -/-knockout mice [12] or in transgenic animals overexpressing a dominantnegative FADD [16][17][18], exhibit a reduced proliferative capacity.…”
Section: Decreased Proliferative Capacity Of Lck Flip S -Transgenic Tmentioning
confidence: 99%
“…In addition, FLIP L expression has been reported to switch CD95-mediated glucose signaling in human pancreatic b cells from apoptosis to cell replication [24]. However, several groups have shown that caspase activity, in particular that of Caspase-8, plays an important role in promoting lymphocyte activation and proliferation [25][26][27][28][29]. In line with these findings and contrary to the study by Lens et al [23], transgenic overexpression of FLIP L in mouse T cells has also been reported to lead to suppression of T cell activation and proliferation as a consequence of FLIP L -mediated inhibition of FADD/Caspase-8 signaling [30].…”
Section: Introductionmentioning
confidence: 99%
“…8,10,12,15,16 Loss of FADD function diminished both the proliferative expansion of immature T cells stimulated through the pre-TCR complex 17 and the response of mature T cells to mitogens 8,10 or antigen. 18 Recently, two siblings exhibiting features of autoimmune lymphoproliferative syndrome (ALPS), a disease that is usually due to mutation in the fas gene, 1 were found instead to have a homozygous mutation in the caspase-8 gene.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, two siblings exhibiting features of autoimmune lymphoproliferative syndrome (ALPS), a disease that is usually due to mutation in the fas gene, 1 were found instead to have a homozygous mutation in the caspase-8 gene. 15 The resulting instability of caspase-8 rendered lymphocytes resistant to Fas-induced apoptosis and surprisingly, B, T and NK cells were also refractory to mitogenic and antigenic stimulation. 15 An essential role for caspase-8 in T-cell activation was proven by the analysis of mice devoid of caspase-8 only in T cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation